LncRNA–miRNA–mRNA ceRNA network of different body colors in Plectropomus leopardus - Hao, Ruijuan; Zhu, Xiaowen; Tian, Changxu; Jiang, Mouyan; Huang, Yang; Li, Guangli; Zhu, Chunhua (Frontiers in Marine Science, 2023)
Long non-coding RNAs (lncRNAs) play a multifaceted role in transcriptional regulation, and the potential molecular regulatory mechanisms of lncRNAs and lncRNA–miRNA–mRNA networks in body color formation are of great significance for its selective breeding. Therefore, lncRNAs and lncRNA-miRNA-mRNA ceRNA network of red- and black-colored Plectropomus leopardus were identified and analyzed. Sequencing analyses identified 167 differentially expressed lncRNAs (DELs) between red- and black-colored P. leopardus, including 89 upregulated and 78 downregulated DELs in the red-colored group (false discovery rate (FDR) < 0.05 and |log2FC| > 1). Differentially expressed miRNA (DEM), genes (DEG), and DEL analyses found 605 and 125 negatively co-expressed miRNA–mRNA pairs and lncRNA–miRNA pairs, respectively. Further correlation analysis with Spearman’s correlation coefficient >0.9 as the threshold identified 3,721 lncRNA–mRNA pairs. Then, a competitive endogenous RNA (ceRNA) network of 325 pairs (p < 0.05) was obtained. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment of network DEGs showed that melanin metabolic process, lipid metabolism, and immune-related pathway were enriched. The ceRNA network provided interactions among lncRNAs, miRNAs, and mRNAs and extended the molecular foundation of body color formation.